Kinematic and dynamic stroke variables of elite and sub-elite rowers - Peric, D.; Ilic, N.; Ahmetovicvic, Z. (International Journal of Performance Analysis in Sport, 2019)
The subject of this research are the kinematic and dynamic stroke variables measurable in real conditions (during regatta speed boat movement in water), as well as basic body dimensions of elite and sub-elite rowers. The aim is to determine the extent to which kinematics and dynamic variables influence on the regatta speed of the boat and whether they can be used to explain the differences between the elite and sub-elite rowers. The sample consisted of four elite rowers (world championship medal winners) and eight sub-elite competitors (quality university rowers). The data regarding all kinematic and dynamic variables were obtained by applying a modern electronic BioRow system that enables automatic data reading in real conditions during rowing. The results obtained indicate that the speed of the boat is mostly correlated with Rowing Power, and then with Finish Angle and Average Force. These three variables had the strongest influence on the differences between the elite and sub-elite rowers. Significant differences between elite and sub-elite rowers were determined for two additional, dynamic (Work per Stroke and Maximum Force) and two anthropometric variables (Body Mass and Body Height). For each of them, the elite rowers had significantly higher average values.